Analysis of the Numerical Results Obtained from the Experimental Examination of the Mechanical Properties of Geopolymer Concrete - Mohammadhossein Mansourghanaei; Alireza Mardookhpour (Numerical Methods in Civil Engineering)
Alkali activated slag concrete (AASC) was introduced to mitigate the environmental damages caused by CO2 emissions and the great level of fossil fuel consumption during cement manufacturing. This type of concrete can demonstrate favorable resistance against mechanical and thermal conditions. In the present investigation, several experimental studies are conducted on alkali activated slag concrete. Accordingly, Nano-silica (NS) particles are used to improve the AASC structure's matrix. The results demonstrate that adding NS to AASC changes the resistance of the sample against heating treatment in the compressive strength test from 16.4 to 8.4%, from 21 to 13% in the tensile strength test, and 41 to 33% in the modulus of elasticity. Besides, the presence of polyolefin fibers (POFs) in the AASC mixture substantially affect tensile strength, and resistance against an impact. In the following, the results Ultrasonic Pulse Velocity (UPV) test compared and evaluated through numerical investigations by conducting UPV tests and analysis SEM, XRD and XRF.